2020
DOI: 10.1186/s40662-020-00191-6
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Descemet stripping automated endothelial keratoplasty versus Descemet membrane endothelial keratoplasty: a fellow-eye comparison

Abstract: Background: To compare the visual outcome and patients' satisfaction after ultrathin Descemet stripping automated endothelial keratoplasty (UT-DSAEK) and Descemet membrane endothelial keratoplasty (DMEK) performed on fellow eyes of the same patients. Methods: In this retrospective study, the records of 18 pseudophakic patients affected by Fuchs endothelial dystrophy who underwent DMEK in one eye and UT-DSAEK in the fellow eye were reviewed. Best corrected visual acuity (BCVA), corneal pachymetry, keratometry, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 32 publications
2
56
0
Order By: Relevance
“…Mencucci et al [ 19 ] compared UT-DSAEK and DMEK in a similar study to ours, finding a difference of 0.023 logMAR favoring DMEK in BCVA. Moreover, clinical significant differences (2.5 letters or more) were considered unlikely among both procedures.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Mencucci et al [ 19 ] compared UT-DSAEK and DMEK in a similar study to ours, finding a difference of 0.023 logMAR favoring DMEK in BCVA. Moreover, clinical significant differences (2.5 letters or more) were considered unlikely among both procedures.…”
Section: Discussionsupporting
confidence: 78%
“…Additionally, they found that contrast sensitivity was higher after DMEK, especially in mesopic conditions and at medium spatial frequencies. Menucci et al [ 19 ] observed that the ECD was higher in the UT-DSAEK group; however, they did not observe statistically significant differences between both techniques. Regarding patient preference, they reported that although most patients were highly satisfied with their vision in both eyes, about one third reported better vision in the eye that underwent DMEK.…”
Section: Discussionmentioning
confidence: 93%
“…This allowed us to assume that the visual rehabilitation of patients after DMEK was shorter than that after UT-DSAEK. Indeed, data provided by Mencucci et al lead to a similar assumption that postoperative recovery after DMEK might be quicker than that after UT-DSAEK [ 7 ]. Our results are also in line with those from the randomized controlled DETECT trial, which documented that DMEK was associated with a postoperative shift in posterior corneal astigmatism but not UT-DSAEK [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few studies that compared DMEK and UT-DSAEK, and they mainly focused on visual acuity outcomes, contrast sensitivity, endothelial cell loss or complication rates [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Some studies also compared the patient-recorded outcome measures between both techniques [ 6 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation